The Negotiations in the Council of the European Union Dataset - Naurin, Daniel; Johansson, Markus; Lindahl, Rutger; Larsson, Olof (University of Gothenburg, 2022)
The dataset is based on telephone surveys that have been conducted every third year between 2003 and 2021. The respondents are representatives of the EU member states to 11 different working groups and committees in the Council of the EU. The purpose of the project is to improve our understanding of international decision-making, negotiations and cooperation with a special focus on the Council of the EU. The survey includes questions that are repeated in all the six survey rounds as well as questions that have been asked one or several times. Some of the questions are survey experiments. The design of the survey makes possible comparisons across policy areas, member states and over time.

Datasetet bygger på en telefonenkät som genomförts vart tredje år mellan 2003 och 2021. Respondenterna är representanter för EU:s medlemsstater i 11 olika arbetsgrupper och kommittéer i EU:s ministerråd. Projektet syftar till att skapa bättre kunskaper om internationella beslutsprocesser, samarbete och förhandlingar med särskilt fokus på den Europeiska Unionen. Enkäten innehåller både frågor som upprepas vid varje mättillfälle och frågor som ställts vid ett eller flera tillfällen. En del av frågorna utgör surveyexperiment. Enkätens upplägg skapar möjligheter för att genomföra jämförande analyser mellan policyområden, medlemsstater och år.
Dataset om förhandlingar i Europeiska Unionens råd
Keywords: european union; europeiska unionen; international cooperation; internationellt samarbete; council of ministers; ministerråd; International politics and organisations; Internationell politik och organisationer; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning)